2009
DOI: 10.1007/s12524-009-0044-4
|View full text |Cite
|
Sign up to set email alerts
|

Advanced analysis of differences between C and X bands using SRTM data for mountainous topography

Abstract: By Interferometric Synthectic Aperture Radar (InSAR), during the Shuttle Radar Topography Mission (SRTM) height models have been generated, covering the earth surface from 56° south to 60.25°n orth. With the exception of small gaps in steep parts, dry sand deserts and water surfaces, the free available US C-band data cover the earth surface from 56°s outh to 60.25° north completely while the X-band data, distributed by the DLR (German Aerospace Center), cover it only partially. The C-band and Xband radar canno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…To date, assessments of the accuracy of SRTM DEMs in mountainous areas have been applied mainly in the context of glacier monitoring (KÄ Ä B 2005;BERTHIER et al 2006;SURAZAKOV and AIZEN 2006;FUJITA et al 2008;FREY and PAUL 2012), hydrological modelling (LUDWIG and SCHNEIDER 2006) and terrain morphometry (GOROKHOVICH and VOUSTIANIOUK 2006;SEFERCIK and ALKAN 2009). However, complex investigations of the factors that can potentially influence the accuracy of SRTM DEMs in mountainous areas, especially for the recently released X-band data, are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…To date, assessments of the accuracy of SRTM DEMs in mountainous areas have been applied mainly in the context of glacier monitoring (KÄ Ä B 2005;BERTHIER et al 2006;SURAZAKOV and AIZEN 2006;FUJITA et al 2008;FREY and PAUL 2012), hydrological modelling (LUDWIG and SCHNEIDER 2006) and terrain morphometry (GOROKHOVICH and VOUSTIANIOUK 2006;SEFERCIK and ALKAN 2009). However, complex investigations of the factors that can potentially influence the accuracy of SRTM DEMs in mountainous areas, especially for the recently released X-band data, are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The SRTM data is freely available in two bands, X and C, at resolutions of 30 and 90 m, and have been used extensively by scientific researchers worldwide in different disciplines. Ever since the release of SRTM data in 2000, many studies have evaluated the quality of this data and all have found it to comply with the SRTM mission goal of 16 m linear error at 90% confidence equivalent to RMSE of ∼ 10 m. Global validation of X-band data has not been carried out although some local studies have validated the X-band data (e.g., Turkey (Sefercik and Alkan 2009) and Poland (Kolecka and Kozak 2013)) and observed that the accuracy of the Xband data was in the same range as C-band SRTM and the latter was marginally more accurate. However, these studies did not use GPS data to test the accuracy of the X-band SRTM data.…”
Section: Discussionmentioning
confidence: 99%
“…As known, the main parameter for most realistic DSM and DTM generation using optical stereoscopy is the number of proper matching and height points that are marked by the operator. The heights of the entire included points in requested grid interval of a DSM or a DTM are automatically calculated by interpolation which decreases the vertical accuracies of them [Passini and Jacobsen, 2007;Sefercik and Alkan, 2009]. The most significant factor that minimizes the negative influence of interpolation is measured point density for the generation area.…”
Section: Methodologies For Image Processing and Building Extractionmentioning
confidence: 99%